Model simulations of early westward flow across the Tasman Gateway during the early Eocene - W. P. Sijp; A. S. von der Heydt; P. K. Bijl (Climate of the Past, 2016)
The timing and role in ocean circulation and climate of the opening of Southern Ocean gateways is as yet elusive. Recent micropalaeontological studies suggest the onset of westward throughflow of surface waters from the SW Pacific into the Australo-Antarctic Gulf through a southern shallow opening of the Tasman Gateway from 49–50 Ma onwards, a direction that is counter to the present-day eastward-flowing Antarctic Circumpolar Current. Here, we present the first model results specific to the early-to-middle Eocene where, in agreement with the field evidence, southerly shallow opening of the Tasman Gateway indeed causes a westward flow across the Tasman Gateway. As a result, modelled estimates of dinoflagellate biogeography are in agreement with the recent findings. Crucially, in this situation where Australia is still situated far south and almost attached to Antarctica, the Drake Passage must be sufficiently restricted to allow the prevailing easterly wind pattern to set up this southerly restricted westward flow. In contrast, an open Drake Passage, up to 517 m deep, leads to an eastward flow, even when the Tasman Gateway and the Australo-Antarctic gulf are entirely contained within the latitudes of easterly wind.